1992
DOI: 10.1161/01.atv.12.11.1267
|View full text |Cite
|
Sign up to set email alerts
|

Time course and cellular characteristics of the iliac artery response to acute balloon injury. An angiographic, morphometric, and immunocytochemical analysis in the cholesterol-fed New Zealand white rabbit.

Abstract: Evaluation of the response of the arterial vessel wall to acute arterial injury in experimental models has taken on substantial importance because of an increasing interest in angioplasty treatment of human atherosclerotic lesions. In this study, the response of normal arterial vessels to acute balloon injury was studied in 45 iliac artery segments from 24 New Zealand White rabbits fed a 2% cholesterol diet. At specified time points between 1 and 41 days after the initial balloon pullback injury, the iliac art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…[26][27][28] We found that MFAP4 promoted CCL2-induced monocyte chemotaxis in an integrin α V β 3 -dependent manner. As monocytes and monocyte-derived macrophages constitute the majority of leukocytes infiltrating neointimal lesions, 29,30 our experiments suggest that reduction in leukocyte influx observed in MFAP4-deficient mice can be explained by impaired monocyte recruitment toward the injury site.…”
Section: Discussionmentioning
confidence: 57%
“…[26][27][28] We found that MFAP4 promoted CCL2-induced monocyte chemotaxis in an integrin α V β 3 -dependent manner. As monocytes and monocyte-derived macrophages constitute the majority of leukocytes infiltrating neointimal lesions, 29,30 our experiments suggest that reduction in leukocyte influx observed in MFAP4-deficient mice can be explained by impaired monocyte recruitment toward the injury site.…”
Section: Discussionmentioning
confidence: 57%
“…Histologically, injury-induced neointimal lesions in these non-cholesterol-fed rabbit models resernble human fibrous coronary plaques (consisting mainly of SMCs and newly-deposited extracellular matrix) and are distinct from lesions in the cholesterol-fed rabbit model (characterized by a large number of lipid-laden macrophages) and post-transplant coronary artherïopathy which is marked with intensive lymphocyte infiltration (226,227). Results from our pilot study demonstrate that suramin significantly inhibits neointimal formation after primary injury of the rabbit iliac artery (Figure 4).…”
Section: Discussionmentioning
confidence: 92%
“…In the transplanted artery, alloimmunity involving T lymphocytes and their consequent recruitment of macrophages seem to be of major importance 51 ; cyclosporine inhibits T lymphocytes. In the balloon-injured artery, smooth muscle cell proliferation 10,26 in response to wound healing and possibly macrophages under conditions with hypercholesterolemia 13,25,30,48 may be of more importance.…”
Section: Discussionmentioning
confidence: 99%